LINGUISTIC LANDSCAPE IN GOA JEPANG BINSARI BIAK PAPUA - Yeni Yulia Andriani; Adelia, Silvy (Language Horizon: Journal of Language Studies, 2025)
Landscape linguistics is a branch of linguistic study that investigates language use within public spaces. Language variation is defined as differences in language use among speakers. The emergence of these variations is influenced by the multilingual and multicultural nature of Indonesian society. This study aims to explore the use of language variation, language contestation, language functions, and the creators of linguistic landscape signs at the tourist destination Goa Jepang Binsari (GJB) in Biak, Papua. Employing a descriptive qualitative research method, data were collected through observation and photography, focusing on images of linguistic landscape signs. The findings reveal five types of language variation at Goa Jepang Binsari, including two monolingual, two bilingual, and one multilingual variation, along with seven instances of language contestation. The creators of the linguistic landscape signs in this area comprise both public authorities and private individuals. The functions of the linguistic landscape at Goa Jepang Binsari include serving as building markers, providing instructions and information, issuing prohibitions and warnings, and facilitating advertising.